Distribuição de espécies de columbídeos (Aves: Coliumbiformes), na zona urbana de Uberlândia, MG - Cândido, Claudiney Rocha (2006)
Among the birds which live in urban environments, we can point out the Columbidae family (pigeons and doves). Due to their ability to adapt, many species of this group became resistant to the human presence and world transformations. The purpose of this study was to find their distribution in the city of Uberlândia, Minas Gerais State, and correlate the occurrence of these species to environmental factors (vegetation, types of buildings and distance to downtown). This work was carried out from March (2005) to February (2006), from 6:30 am to 9:30 am. We selected six species of Columbidae found in the city: Columba livia (rock pigeon), Patagioenas picazuro, P. cayennensis, Zenaida auriculata, Columbina talpacoti and Columbina squammata. The data were collected in 24 squares selected from the urban area, during dry and rainy seasons. In order to quantify the records, we made 12-minute observation sessions in each square, totalizing 434 sessions and 86.8 hours of observation. The frequency of records in each session was calculated by dividing the frequency of records of each species by the time of the session. We used the Mantel test to make the cluster analysis and the correlation between the species composition and the environmental factors. All the species under study were recorded. The Z. auriculata showed the highest mean frequency of records ( X =2.0±1.6), being more frequently found downtown ( X =2.7±1.6), rather than in periphery ( X =1.3±0.6). Only in one square (Anahyta Tannus Square) all the species were recorded. The mean frequency of record of Columbidae was higher in central rather than peripheral areas, as much in rainy ( X downtown=0.7±1.2; X periphery=0.5±0.6) as in dry seasons ( X downtown=0.9±1.9; X periphery=0.3±0.8). We observed higher mean frequency of records during dry season. The analysis of composition of each grouping showed the formation of a group containing the major part of the central squares considered separately; however, some central squares were grouped with peripheral ones. Only the distance to downtown was significantly correlated to the distribution of Columbidae species in the urban area of Uberlândia (r=0.2111; p<0.05). These results suggest a probable association of the pigeon distribution with urbanization.